Fibrous Proteins : Coiled-Coils, Collagen and Elastomers - Parry, D. A. D.; Squire, John, 1945- (Advances in protein chemistry ;, 2005)
Fibrous Protein: Coiled-Coils, Collagen and Elastomers is the first of a three-part series on Fibrous Proteins. The books are based on a very successful workshop in Alpbach, Austria on the general topic of Fibrous Proteins that gave rise to the award winning issue of Journal of Structural Biology. Part II will contain an extensive discussion of Molecular Motors and Muscle, Part III on Amyloids, Prions and Beta Proteins. Advances in Protein Chemistry is available online on ScienceDirect - full-text online of volumes 53 onwards. *Reveals new structural and functional aspects of fibrous proteins *Based on Fibrous Protein workshop in Alpbach, Austria that gave rise to 2003 Nobel Prize winners in Chemistry.